No longer an orphan: evidence for appositive attachment from sentence comprehension. Issue 1 (5th March 2018) - Dillon, Brian; Frazier, Lyn; Clifton, Charles
Abstract : In this paper, we investigate the comprehension of appositive relative clauses and nominal appositives. First, we present experimental evidence that suggests that nominal appositives and appositive relative clauses behave like other adjunct phrases with respect to ambiguity resolution (Experiment 1). Second, we show that an ambiguous nominal appositive can modify a distant syntactic head as easily across an appositive relative clause as across a restrictive relative clause (Experiment 2). Last, we show that syntactic repair is as successful across an appositive relative clause or parenthetical as it is across an at-issue restrictive relative clause (Experiment 3). Taken together, our results suggest that i) appositive relative clauses and nominal appositives are syntactically sited in a fashion comparable to restrictive relative clauses and ii) appositive phrases do not substantially reduce the availability of the syntactic material that precedes the appositive phrase as might have been expected if processing an appositive involved shifting attention to a higher structure, away from local preceding constituents. These results constitute an argument from sentence comprehension for a local syntactic attachment of appositive relative clauses and nominal appositives (cf. Jackendoff 1977 ; Potts 2005 ; de Vries 2006 ), and against so-called orphan analyses of appositive content (e.g. Ross 1967 ; Haegeman 1988 ).